Odpowiedzialność społeczna jako kategoria współczesnej teorii... - Niemiec, Barbara (Horyzonty Wychowania, 2017)
The article presents the analysis of the concept of responsibility on the basis of contemporary philosophical thought, showing, at the same time, its pedagogical implications. It constituted the starting point for defining the notion of social responsibility as a kind of relation linking the doer with his deed, being the answer to some value and/or its consequences and revealing the following features: – the doer is collective entity, – the doer is an individual but his deed and/or its consequences refer to the social addressee, – the subject of responsibility is another man, community, common good; one can also refer to social responsibility in the case its subject is the doer or his personal property for the sake of social consequences of the deed, – the instance imposing responsibility is community, articulated through the accepted system and hierarchy of values, current norms, customs, models of roles and holding dignity, – the executor is community equipped with sanctions in the form of informal rewards and punishments. The article expresses the reflection upon the need and possibilities of shaping the above-defined social responsibility in the light of contemporary tendencies in theory and practice in education as well as the context of social life.